INFORMATION-ANALYTICAL MONITORING SYSTEM OF PROFESSIONAL EDUCATION QUALITY - Alexander I. Mitin; Tatyana A. Filicheva (Открытое образование (Москва))
Article opens a series of publications devoted to creation of information-analytical system of monitoring of professional training quality which provides the solution of expert and analytical problems of an assessment of current state of quality of educational services, formation of recommendations about improvement of quality for administration of educational institution.